2017
DOI: 10.1155/2017/4985323
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Heme Oxygenase-1 in Mesenchymal Stem Cells Augments Their Protection on Retinal Cells In Vitro and Attenuates Retinal Ischemia/Reperfusion Injury In Vivo against Oxidative Stress

Abstract: Retinal ischemia/reperfusion (I/R) injury, involving several ocular diseases, seriously threatens human ocular health, mainly treated by attenuating I/R-induced oxidative stress. Currently, mesenchymal stem cells (MSCs) could restore I/R-injured retina through paracrine secretion. Additionally, heme oxygenase-1 (HO-1) could ameliorate oxidative stress and thus retinal apoptosis, but the expression of HO-1 in MSC is limited. Here, we hypothesized that overexpression of HO-1 in MSC (MSC-HO-1) may significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
(52 reference statements)
3
16
0
Order By: Relevance
“…102,103 The preservation of ELECTRICAL ENRICHMENT OF HMSCS stemness remains one of the priorities in many in vitro investigations with the assumption that a more stem-like state correlates with better therapeutic immunomodulation. We found that MSC-DC H had elevated mRNA expression of HO-1, a rate-limiting enzyme in heme metabolism, with anti-inflammatory, antioxidative, and antiapoptotic functions, 104,105 as well as pleiotropic cytokine IL-6, which is heavily involved in the immunomodulatory function of MSCs. However, after 24 h of culture of EE-hMSCs, we observed a shift toward greater expression of HO-1 and IL-6 in MSC-DC L .…”
Section: Discussionmentioning
confidence: 88%
“…102,103 The preservation of ELECTRICAL ENRICHMENT OF HMSCS stemness remains one of the priorities in many in vitro investigations with the assumption that a more stem-like state correlates with better therapeutic immunomodulation. We found that MSC-DC H had elevated mRNA expression of HO-1, a rate-limiting enzyme in heme metabolism, with anti-inflammatory, antioxidative, and antiapoptotic functions, 104,105 as well as pleiotropic cytokine IL-6, which is heavily involved in the immunomodulatory function of MSCs. However, after 24 h of culture of EE-hMSCs, we observed a shift toward greater expression of HO-1 and IL-6 in MSC-DC L .…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, overexpression of proteasome subunit beta 5 (PSMB5) maintains the differentiation capacity of late‐passage MSCs, even under exposure to H 2 O 2 , and overexpression of heme oxygenase 1 in MSCs significantly attenuates H 2 O 2 ‐induced injury of retinal ganglion cells by decreasing levels of cellular ROS and proapoptotic proteins. Thus, modified MSCs are highly effective at attenuating retinal I/R injury by maintaining structural thickness and decreasing apoptosis . In addition to general virus‐mediated overexpression of critical genes, microRNAs (miRNAs) and small molecules contribute to the regulation of MSC activities by modulating ROS levels.…”
Section: Strategies To Control Ros Levels For Msc Fates In Vitro and mentioning
confidence: 99%
“…34,52 Our TUNEL results suggest that CoPP is sufficient to alleviate the photoreceptor apoptosis in MNU-administered mice. A previous study 53 also has shown that HO-1 overexpression inhibits RGC apoptosis in ischemic retinas. CoPP treatment can enhance Bcl-2 expression and adjust the Bcl/Bax ratio toward a net ''antiapoptotic'' effect.…”
Section: Discussionmentioning
confidence: 78%